ECPPM 2021 - eWork and eBusiness in architecture, engineering and construction : proceedings of the 13th European Conference on Product & Process Modelling (ECPPM 2021), 5-7 May 2021, Moscow, Russia /: proceedings of the 13th European Conference on Product & Process Modelling (ECPPM 2021), 5-7 May 2021, Moscow, Russia. (2021) - Unknown
No abstract available